Pendekatan Kajian Islam dalam Kitab Akhlaqul Banin pada Anak Usia Madrasah Ibtidaiyah - Wahid Khoirul Anam; M. Choirul Muzaini (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
The purpose of this study was to examine the relevance of Islamic studies in the book Akhlaqul Banin Juz I by 'Umar bin Achmad Baraja' in children aged Madrasah Ibtidaiyah (MI). This research is a qualitative research type of literature, data collection techniques with observation and documentation, in data analysis techniques researchers use source triangulation. The results of the study are: The book of Akhlaqul Banin volume 1 contains the contents of children's moral education in everyday life which consists of several chapters, and is classified into two parts, namely: akhlakul mahmudah namely good morals that are in line with the teachings of Islam, namely the Qur'an and Hadith. Examples of easy nature are, patient, grateful, humble, helpful. and the morality of the mazmumah is linguistically despicable. Disgraceful morals are all forms of actions that are contrary to commendable morals. Examples of madzmummah morals are, pitting against each other, backbiting, liars or liars, arrogant. In the book of Akhlaqul Banin juz I, it is very relevant to the approach to Islamic studies in children aged Madrasah Ibtidaiyah (MI), because in the book Akhlaqul Banin it is explained in detail about the procedures for having morals to Allah, to the Prophet Muhammad as the Prophet of Allah, morals to parents, mothers and fathers, morals to brothers and sisters. , as well as having morals to teachers and friends at school, all of these explanations have been explained in the Qur'an and sunnah which are the main sources of Islamic teachings.